Genetic structure of Anopheles darlingi Root, An. nuneztovari Gabaldon and An. marajoara Galvão & Damasceno from Colombia using RAPD-PCR - POSSO-G., CARMEN ELISA; GONZÁLEZ-O., RANULFO; CÁRDENAS-H., HEIBER; TASCÓN, RICARDO (Revista Colombiana de Entomología, 2006)
The genetic variation and structure of Colombian populations of three malaria vectors were analyzed by RAPD-PCR. Analysis included mosquito populations from different geographical areas: (1) For An. darlingi, populations from Medio Atrato, Granada and Tierralta; (2) for An. nuneztovari, populations from Buenaventura, Tierralta and Tibú, and (3) for An. marajoara, populations from Fuente de Oro, San Carlos de Guaroa, Yaguará and Cúcuta. Similar collection protocols were followed for using protected human bait and for DNA extraction. The expected heterozygosity of the three species varied from 0,28 to 0,34. The migration/generation rates among populations of each species varied between 1,7 and 30,4. The AMOVA values revealed little genetic structure; between 8,30 and 11,31% of the variation was explained by differences between populations of each species. In general, the populations of each of these species in Colombia display random mating, with a greater gene flow according to degree of geographical separation. FST and ST values for An. darlingi and An. nuneztovari confirmed that the higher genetic flow occurred among western populations (Buenaventura, Medio Atrato, and Tierralta) and for An. marajoara among the eastern populations (Cúcuta, Fuente de Oro, and San Carlos de Guaroa).